POLITIK PLURALISME HUKUM DALAM HUKUM UNDANG-UNDANG KEKUASAAN KEHAKIMAN : KAJIAN TERHADAP PENGAKUAN HUKUM TIDAK TERTULIS DALAM UNDANG-UNDANG NOMOR 48 TAHUN 2009 TENTANG KEKUASAAN KEHAKIMAN - Jamin, Mohammad (Yustisia, 2012)
AbstractIt is empirical fact in Indonesia not only has written  law which imposed by state power ( state law). Beside written law there is also unwritten law  which often called the non state law. Political of law to  uniting as one political unity and enforce the legal sentralism has disregarded the  fact of legal pluralism ( the political of ignorance). Political of law  of the Judicial Power Code  which imposed during the time does not clearly arrange the state recognation to unwritten law, even unwritten law is recognnized, but still very sumir and floating. Although  Code No. 48/2009 about Judicial Power adopt the politics of legal pluralism and recognizes the existence unwritten law, but it is still sham (weak legal pluralism), causing that in fact predominate the state law still happened and unwritten law only becoming complement to state law. Political forwards legal pluralism in   Judicial Power Code ideally is not made conditional. The   political legal  pluralism of Judicial Power Code must to adopt strong legal pluralism,  so can accommodate pluralism in society.